Development of a Novel Therapeutic Suppressor of Brain Proinflammatory Cytokine Up-Regulation That Attenuates Synaptic Dysfunction and Behavioral Deficits - Hu, Wenhui (2006)
We report the development of a novel, aqueous-soluble, safe, small molecule, experimental therapeutic that suppresses injury-induced, proinflammatory cytokine increases in the brain, with resultant attenuation of synaptic protein biomarker loss and improvement in hippocampus-dependent behavioral deficits. A GMP production scheme for the active pharmaceutical ingredient, compound 17, is presented. The development and large-scale availability of this novel compound allow exploration of new, potentially disease-modifying, therapeutic approaches to CNS disorders.